PENERAPAN PSAK NO.30 MENGENAI PERLAKUAN AKUNTANSI SEWA DAN PENGARUHNYA PADA LAPORAN KEUANGAN PT. BFI FINANCE INDONESIA, TBK. - Alipudin, Asep; Ningsi, Rati Pitria (Universitas Pakuan, 2015)
This study was to determine (1) The treatment of lease transactions recorded by PT. BFI Finance Indonesia, Tbk. during the leasing period, (2). Comparing the accounting treatment of lease during the leasing period between conducted by PT. BFI Finance Indonesia, Tbk. with SFAS No. 30 (3). Knowing the impact of lease accounting treatment carried out by PT. BFI Finance Indonesia, Tbk to the Companys Financial Statements. This type of research that used in this research is quantitative descriptive analysis (non-statistical). The data that used were the financial statements. BFI Finance Indonesia, Tbk. during the period 2011 to 2013, the independent variable SFAS No. 30 regarding the accounting treatment of leases. The dependent variable is the effect on the financial statements BFI Finance Indonesia, Tbk. The research is shows that the accounting treatment applied by PT. BFI Finance Indonesia, Tbk on assets acquired through financing activities is by using finance leases (capital leases) and in depreciation by the straight-line method or straight-line method. Treatment as a capital lease is in accordance with SFAS No. 30 but in the lease transaction recording by the company shows the approximate recording errors and grouping. This will affect the fairness of the financial statements performance therefore necessary adjusting entries to correct those mistakes.Â Keywords: Adoption of PSAK No. 30